CYBERNETIC AND SYNERGISTIC MANAGEMENT IMPERATIVES FOR TRADE BUSINESS - Е. Е. Мазур (Ринкова економіка: сучасна теорія і практика управління, 2017)
Trade is one of the most important sectors of human economic activity and it requires some stimulating public regulation, especially in economy under reforms. What kind of impact it should be – the question is still open. In the paper the analysis of an effective system of managing the trading business is being developed. The article presents the creative integration of scientific principles of institutionalism, cybernet-ics, synergy and system approach, which have been adapted for the theory of trade entrepreneurship. The author proceeds from the fact that the trade business is such a complex socio-economic system that the strategies of borrowing patterns of trade organizations from the other countries is poor-ly applicable to it. Thus it is proposed to develop management mechanisms considering the fundamen-tal principles of cybernetics as a body of knowledge about the basics of management system scientific building, as well as taking into account the laws of self-organization of nonlinear socio-economic sys-tems, studied in the framework of synergetic theory. In fact, management is represented as a cybernetic system and the object of management (trading business) - as a social and economic institution that is developing under the laws of self-organization. It is shown that the leading function of state managing the object of research should be focused on creating a favorable regulatory, financial, tax, investment, social and other conditions for trade ac-tivities. The methodological imperatives of management of trade development have been created as the basic requirements for the organization of the control subsystem. Special attention is paid to attractors, resonance zones and points of self-organization of trading business.